Marketing Strategy Analysis to Increase Income Using SWOT and Analytical Hierarchy Process (AHP) (Case Study: Sablon Dzain Art) - Fadillah, J.J.Z Hariadi; Tosungku, La Ode Ahmad Safar; Pawitra, Theresia Amelia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Dzain Art is a business that offers  clothing screen printing services. The development of Dzain Art's business has not been optimal due to its relatively small income. The marketing strategies employed have not been optimal in attracting the market's interest in using clothing printing services. The right marketing strategy will influence potential customers to use the offered clothing printing services, which will have a positive impact on the business's development. Designing a marketing strategy using the SWOT method to formulate strategies that can be applied in marketing clothing printing and the Analytical Hierarchy Process (AHP) method to prioritize the best marketing strategies for Dzain Art. Score of the Internal Factor Evaluation (IFE) Matrix is 3.0118 and the score of the External Factor Evaluation (EFE) Matrix is 2.6765. Dzain Art's position based on the IE Matrix is in Quadrant IV, which indicates that the clothing printing business is in the Growth and Build condition. In Growth and Build position, Dzain Art is suitable for implementing intensive and integrative strategies. The formulation of marketing strategies on the SWOT Matrix produces nine marketing strategies that can be implemented to market clothing printing. The priority order of marketing strategies that Dzain Art can apply in marketing clothing screen printing using the Analytical Hierarchy Process (AHP) method is increasing and expanding collaboration with institutions or communities in providing uniform clothing,second priority is enhancing promotion through social media, and third priority is utilizing digital printing production equipment.